The national multi-center artificial intelligent myopia prevention and control project - Wang, Xun; Yang, Yahan; Wu, Yuxuan; Wei, Wenbin; Dong, Li; Li, Yang; Tan, Xingping; Cao, Hankun; Zhang, Hong; Ma, Xiaodan; Jiang, Qin; Zhou, Yunfan; et al. (Intelligent medicine, 2021)
In recent years, the incidence of myopia has increased at an alarming rate among children and adolescents in China. The exploration of an effective prevention and control method for myopia is in urgent need. With the development of information technology in the past decade, artificial intelligence with the Internet of Things technology (AIoT) is characterized by strong computing power, advanced algorithm, continuous monitoring, and accurate prediction of long-term progression. Therefore, big data and artificial intelligence technology have the potential to be applied to data mining of myopia etiology and prediction of myopia occurrence and development. More recently, there has been a growing recognition that myopia study involving AIoT needs to undergo a rigorous evaluation to demonstrate robust results.